Uji antibakteri teh hitam dan teh hijau kombucha pada methicillin-resistant Staphylococcus aureus (MRSA) - Pramesti, Cyrilla Angelica Andhika; Khikmah, Nur; Sulistyani, Nunung (Jurnal Biologi Udayana; Vol 26 No 1 (2022): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2022.v26.i01.p12, 2022)
Kombucha tea has antibacterial activities against Gram-negative, Gram-positive bacteria, and antibiotic resistant bacteria. Methicillin-resistant Staphylococcus aureus (MRSA) is a strain of Staphylococcus aureus bacteria that has resistance to antibiotics. MRSA is the main cause of nosocomial infections and various clinical syndromes. This study aimed to determine the antibacterial of kombucha tea and the difference in antibacterial effect between kombucha green tea and kombucha black tea in inhibiting MRSA. Kombucha green tea and kombucha black tea were made by fermenting liquid. The kombucha tea antibacterial test on MRSA was determined using well diffusion method. The antibacterial differences between kombucha black tea and kombucha green tea were analyzed by using t-test. Kombucha green tea has a higher total acid content with a lower pH than black kombucha tea. Kombucha black tea and kombucha green tea antibacterial activities on MRSA were shown by an irradiance zone, with a diameter of 14 ± 0,85 mm and 17 ± 0,93  mm. Irradical zone shows that the activities of kombucha black tea and kombucha green tea is categorized as weak. Therefore, kombucha tea has not been effective as an antibacterial against MRSA.  The results of t-test showed that there were differences in antibacterial activities between kombucha green tea and kombucha black tea against Methicillin-resistant Staphylococcus aureus (MRSA).